The Factors Influencing the Effectiveness of e-Learning at Al-Quds Open University in Palestine - Alakklouk, Sari A. A. (2012)
This study examines the factors influencing the effectiveness of e-learning At Al-Quads Open University In Palestine. The study was a cross sectional study where respondents’ perceptions was measured at one point in time (211). Correlation analyses, was to find out whether there is a relationship between e-learning effectiveness as a variable independently, and the Instructor characteristics, student characteristics, technology, and impediments are the dependent variable, At Al-Quads Open University In Palestine. Students’ characteristics such as students’ motivation to use e-learning technology and students’ computing competency have also found to be related with e-learning effectiveness. As compared with the instructor and students’ characteristics, technology and impediments quality in terms of access, navigation, interface and the reliability effectiveness of technology infrastructure have the highest relation to e-learning effectiveness. In conclusion, the results from this study indicate that instructor characteristics, student characteristics, technology, and impediments have strong relationships with e-learning effectiveness.